Perceived Subjective Stress and its Association with 5-min Electrocardiogram-based Heart Rate Variability in Middle-aged Women of an Urban Area of West India - Jayesh Dalpatbhai Solanki; Krina Ashish Atodaria; Divyang Rajeshkumar Joshi; Chhaya Maheshbhai Ghodadara; Jinesh Parmar (Journal of Mid-Life Health, 2025)
Background: Midlife health poses stress to women. Perceived Stress Scale (PSS) score allows subjective assessment of perceived stress whereas heart rate variability (HRV) gives electrocardiogram (ECG)-based quantification of cardiac autonomic function, but the relation between these two is scarcely studied. Hence, the association between PSS and HRV was studied in middle-aged women. Methodology: A cross-sectional study was done in midlife premenopausal (n = 51), perimenopausal (n = 59), and postmenopausal (n = 82) women. Perceived stress was interviewed by PSS score. ECG-based 5 min HRV was done by Variowin HR Software for frequency domain, time domain, and geometric HRV parameters. PSS and HRV were further compared or associated in subgroups, taking P < 0.05 as statistically significant. Results: HRV was reduced in all three groups which had a prevalence of PSS grade 0, 1, 2 44%, 53%, and 3%, respectively, without intergroup difference. Diabetic and/or hypertensive subgroups exhibited reduced HRV than nondiabetic nonhypertensive subgroups. No significant correlation was found between PSS score and HRV parameters in either group. HRV did not associate with PSS grade-based subgroups in pre-, peri-, or postmenopausal stage. Conclusion: Lack of HRV to perceived subjective stress association was observed in 40–55-year-old women with mild confounding by diabetes and/or hypertension. We suggest HRV total power and low-frequency: high-frequency ratio as best HRV parameters and consideration of age, reproductive health stage, and presence of comorbidities as a weak confounder for both HRV and PSS studies of middle-aged women. Further studies are warranted to consolidate the utility of HRV and PSS for the assessment of these two different types of stress.